ENDOMETRIAL STROMAL SARCOMA IN AN ABATTOIR GENITALIA OF A BUFFALO (BUBALUS BUBALIS) - ANUSHA, K; KRISHNA, K MOULI; SRILATHA, CH (The Indian Journal of Animal Reproduction, 2023)
A case of Endometrial Stromal Sarcoma in an abattoir genitalia of buffalo has been reported.